Analisis Efektifitas Metode Pengajaran PAI dalam Meningkatan Nalar Kritis Siswa SMA Negeri Kalimantan Barat - Masruri Masruri; Nanang Zakaria; Muhammad Faisal; Sobirin Sobirin; Hema Malini (Permata : Jurnal Pendidikan Agama Islam, 2024)
The aim of this research is to analyze the effectiveness of Islamic religious education teaching methods in increasing the critical reasoning of public high school students in West Kalimantan. This research method is qualitative research. Qualitative research is a research method used to understand social phenomena in depth. Researchers use this type of research, specifically case studies. This type of research allows researchers to explore perspectives, experiences, and meanings that may be hidden in the data collected in relation to analyzing the effectiveness of PAI teaching methods in improving the critical reasoning of state high school students in West Kalimantan. Meanwhile, the research subjects were two PAI teachers from different high schools. The results of the research show that the quality of teachers and teaching methods in PAI classes is still a major concern. Learning methods that tend to be conventional and less interactive can affect students' involvement and critical reasoning. Students' interest in religious subjects tends to be low, partly due to the perception that the teaching material is less relevant to everyday life and the lack of student involvement in learning. Effective for improving students' critical reasoning.Keyword : Teaching Methods; Islamic Religious Education; Critical Reasoning